Solid type primary intraosseous squamous cell carcinoma in a cat - Pavlin, Darja (BMC Vet Res, 2018)
BACKGROUND: Squamous cell carcinoma (SCC) is the most common nonodontogenic oral tumor in cats. In the jaw, it usually presents as an ulceroproliferative lesion associated with enlargement of the affected bone. CASE PRESENTATION: This report describes the case of a cat in which clinical and radiographic findings of a mandibular swelling were suggestive of an aggressive process, but the oral mucosa was unaffected. The results of histopathological and immunohistochemical examination of the samples obtained from the intraosseous lesion were consistent with SCC. The animal was euthanized 5 months after initial presentation as a result of the severe progression of the disease, and no other primary tumors were identified at necropsy. CONCLUSIONS: Based on the clinicopathological, microscopic, and immunohistochemical staining features, as well as the absence of a primary tumor at a distant site, we propose that the term, solid type primary intraosseous SCC (PIOSCC), be used to describe this neoplasia, as it shares similar features with human PIOSCC.